Upaya Penguatan Pemahaman Kepala MTs di Kota Bandung Setelah Diklat terhadap PMA 58/2017 melalui Pendampingan pada Semester Genap Tahun Pelajaran 2017/2018 - Tony Sudjarwo (Jurnal Pendidikan Madrasah, 2018)
AbstractThis study aims to determine the level of understanding and follow-up plan of headmasters of MTs in Bandung after workshop on PMA 58/2017 through mentoring in the Even Semester 2017/2018 Academic Year. The study was conducted in April to June 2018 in 7 (seven) headmasters of MTs had participated in the workshop on January 29 to February 3, 2018 at BDK Bandung. The headmasters are given 2 (two) actions using the mentoring method by examining the contents of PMA 58/2017 in the form of texts and videos. The level of understanding was measured using knowledge test instruments as many as 20 questions and questionnaires on the level of self-understanding, and Follow-Up Plans (RTL) were measured using RTL filling sheets. Correct scores from knowledge test results are changed to 100 scale values, then made very good categories (values 90-100), good (80-89), sufficient (70-79), less (60-69), and bad (less from 59). Compilation of RTL is assessed based on the plan for pouring 3 (three) main tasks of the headmaster of Madrasah. The results show the level of understanding of 7 headmasters of MTs guided by Pre-Cycle knowledge tests until Cycle II increases. Increasing the value of the Pre-Cycle knowledge test until Cycle II is the lowest 25 and the highest 75 with an increase in the average value of 49.3. The accompanying results in the first cycle of knowledge tests averaged 60, and the second cycle of knowledge tests averaged 77.1, increasing steadily from the Preknowledge test cycle state averaging 33.6. The average category of knowledge test results in the Cycle II (final) category is Less 1 person, Enough 3 people, and Good 3 people. The level of overall understanding according to oneself is 72.7 categories Enough. The 100% follow-up plan was prepared by verification of initial physical evidence which reached 72.6. Level of understanding and plan for following up headmasters of MTs in Bandung after worshop towards PMA 58/2017 through mentoring in the Even Semester 2017/2018 Academic Year increased in the Enough category. Keywords: Strengthening, Understanding, Mentoring, Headmaster of MTs AbstrakPenelitian bertujuan untuk untuk mengetahui tingkat pemahaman dan rencana tindak lanjut Kepala Madrasah Tsanawiyah di Kota Bandung setelah Diklat Kepala Madrasah terhadap PMA 58/2017 melalui pendampingan pada Semester Genap Tahun Pelajaran 2017/2018. Penelitian dilakukan di bulan April sampai dengan Juni 2018 pada 7 (tujuh) Kepala Madrasah MTs binaan yang telah mengikuti Diklat Kepala Madrasah yang diselenggarakan tanggal 29 Januari sampai 3 Februari 2018 di BDK Bandung. Kepala Madrasah diberikan tindakan menggunakan metodependampingan sebanyak 2 (dua) kali dengan cara telaah isi PMA 58/2017 bentuk naskah dan video. Tingkat pemahaman diukur menggunakan instrumen uji pengetahuan sebanyak 20 pertanyaan serta kuesioner tingkat pemahaman menurut diri sendiri, dan Rencana Tindak Lanjut (RTL) diukur menggunakan lembar pengisian RTL. Skor benar hasil uji pengetahuan dikonversi menjadi nilai skala 100, lalu dibuat kategori amat baik (nilai 90-100), baik (80-89), cukup (7079), kurang (60-69), dan buruk (kurang dari 59). Penyusunan RTL dinilai keberadaannya berdasarkan penuangan rencana 3 (tiga) tugas pokok Kepala Madrasah. Hasil menunjukkan tingkat pemahaman 7 Kepala Madrasah MTs binaan berdasarkan uji pengetahuan Pra Siklus hingga Siklus II meningkat. Peningkatan nilai uji pengetahuan Pra Siklus sampai Siklus II terendah 25 dan tertinggi 75 dengan rata-rata peningkatan nilai sebesar 49,3. Hasil pendampingam di Siklus I uji pengetahuan rata-rata 60, dan Siklus II uji pengetahuan rata-rata 77,1, meningkat terus dari keadaan Pra Siklus uji pengetahuan rata-rata 33,6. Rata-rata Kategori hasil uji pengetahuan di Siklus II (akhir) kategori Kurang 1 orang, Cukup 3 orang, dan Baik 3 orang. Tingkat pemahaman keseluruhan menurut diri sendiri sebesar 72,7 kategori Cukup. Rencana tindak lanjut 100% tersusun dengan verifikasi bukti fisik awal mencapai 72,6. Tingkat pemahaman dan rencana tindak lanjut Kepala Madrasah Tsanawiyah di Kota Bandung setelah Diklat Kepala Madrasah terhadap PMA 58/2017 melalui pendampingan pada Semester Genap Tahun Pelajaran 2017/2018 meningkat dalam kategori Cukup. Kata Kunci: Penguatan, Pemahaman, Pendampingan Kepala MTs